The Killing of Women in “Sex Games Gone Wrong”: An Analysis of Femicides in Great Britain 2000–2018 - Yardley, Elizabeth (Violence against women, 2021)
This research investigated cases of femicide in Great Britain where perpetrators claimed that victims died in “sex games gone wrong.” Forty-three femicides that resulted in a conviction for murder, manslaughter, or culpable homicide were examined in relation to victim–perpetrator sociodemographic characteristics, victim–perpetrator relationship, homicide details, and criminal justice outcomes. Key patterns within the data were identified. The research highlights that the “sex game gone wrong” narrative has gained traction against a cultural backdrop of normalized bondage, domination, and sadomasochism (BDSM) within neoliberal political economy.